Nurses' knowledge, attitudes and practices regarding influenza vaccination: an integrative review. Issue 19 (21st May 2016) - Smith, Sarah; Sim, Jenny; Halcomb, Elizabeth
Abstract : Aims and objectives: To critically analyse the literature describing nurses' knowledge, attitudes and practices regarding influenza vaccination. Background: Influenza is a serious illness that has significant impacts on productivity, health outcomes and healthcare costs. Despite the recommendations for nurses to be vaccinated annually against influenza, the vaccination rates remain suboptimal. Design: Integrative literature review. Methods: An integrative review was conducted as described by Whittemore and Knafl (2005). A search of CINAHL, Cochrane Library, ProQuest Central, ClinicalKey, ScienceDirect, Wiley Online Library, and Informit was undertaken to identify relevant papers. Given the heterogeneity of included studies, a narrative approach was used to analyse the data. Results: There was limited research available on this topic area, with only 10 papers identified as meeting the inclusion criteria. Five themes were identified: the relationship between knowledge and influenza vaccination, perception of risk, motivators for influenza vaccination, barriers to influenza vaccination and impact of demographics on vaccination. Conclusions: Despite the evidence for the protective effects of influenza vaccination, rates of vaccination among nurses remain sub‐optimal. Nurses' influenza vaccination practices likely relate to their level of knowledge and perception of risk; the greater nurses' knowledge regarding influenza and influenza vaccination the higher their perception of risk and the more likely they are to be vaccinated. This also translates to the advice that they give patients with vaccinated nurses more inclined to recommend vaccination than those unvaccinated. Relevance to clinical practice: The practices of nurses related to influenza vaccination may translate to the advice that they give their patients. Understanding the knowledge levels, practices and attitudes of nurses can assist in developing strategies to enhance education of nurses.